DAMPAK PARIWISATA TERHADAP PERUBAHAN SOSIAL MASYARAKAT DI DESA TONGKE-TONGKE KABUPATEN SINJAI (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
This study entitled The Impact of Tourism on Social Change in the Village of Tongke-tongke, Sinjai Regency. This study aims to determine the socio-economic impact caused by tourism on the lives of the surrounding community. In this study, the author uses a descriptive qualitative research type, where qualitative research is one of the studies that produces descriptive data in the form of speech or writing and the behavior of the people observed, the authors use a sociological and social welfare approach. The data sources used are primary and secondary, while primary data is obtained through direct interaction in the field with informants through interviews and observations and secondary data is obtained from documentation to complete primary data. Data collection methods used are observation, interviews, and documentation. The informants of the research were seasonal farmers, pump heads, and the community in Jalanjang sub-district. Based on the results of interviews, observations, and documentation of the author while in Tongke-tongke Village, the results of this study indicate that, the forms of social change due to the development of tourism in the Tongke-tongke village community, Sinjai district, amounted to 3, namely: 1. Opening jobs 2. Development 3. Encourage someone to become an entrepreneur. The impact of tourism on social change in the Tongke-tongke community is twofold, namely: 1 social interaction. and 2.LifestyleThe implications of this research are 1. So that people maintain the cleanliness of tourist sites so that tourists feel comfortable. 2. Pemerinta Conduct socialization and education to tourism managers to find out what tourists need when visiting.